HUBUNGAN TINGKAT PENGETAHUAN TERHADAP KEPATUHAN SAFETY RIDING PADA REMAJA DI SMA NEGERI 8 BALIKPAPAN - Zainul, L.M. (IDENTIFIKASI, 2020)
Driving a motorcycle needs to be supported by good driving knowledge, so that traffic order can be carried out so that road safety can be realized, besides that the enforcement of driving standards needs to be considered such as the use of helmets and driving documents. This study aims to determine the relationship of the knowledge variable (X) to the safety riding compliance variable (Y) of students of SMAN 8 Balikpapan. The method in this study using quantitative methods with a total sample of 54 students of class XII from a population of 120 students. Samples were taken randomly from two majors, namely natural Science and Social Sciences. Based on the results of the research sample test, all are valid and reliable and there is a significant relationship between the X variable and the Y variable with a P-value of 0.018. The conclusion of the research conducted on students of SMAN 8 Balikpapan that there is a significant relationship between the level of knowledge and compliance with safety riding.